1993
DOI: 10.1128/aem.59.12.4044-4050.1993
|View full text |Cite
|
Sign up to set email alerts
|

Selective Adhesion of Thiobacillus ferrooxidans to Pyrite

Abstract: Bacterial adhesion to mineral surfaces plays an important role not only in bacterial survival in natural ecosystems, but also in mining industry applications. Selective adhesion was investigated with ThiobaciUus ferrooxidans by using four minerals, pyrite, quartz, chalcopyrite, and galena. Escherichia coli was used as a control bacterium. Contact angles were used as indicators of hydrophobicity, which was an important factor in the interaction between minerals and bacteria. The contact angle of E. coli in a 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(32 citation statements)
references
References 31 publications
4
27
0
1
Order By: Relevance
“…It was also observed that a greater proportion of the chalcopyrite was preferentially bioleached over the silicates. This is supported by the preferential attachment of acidophiles to sulfide minerals suggesting that these are their natural growth substrates (Edwards et al, 1999;Murr and Berry, 1976;Ohmura et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…It was also observed that a greater proportion of the chalcopyrite was preferentially bioleached over the silicates. This is supported by the preferential attachment of acidophiles to sulfide minerals suggesting that these are their natural growth substrates (Edwards et al, 1999;Murr and Berry, 1976;Ohmura et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…The biofilm formation screen described above was performed using microtitre dishes composed of PVC. However, it is clear that bacteria form biofilms on a wide range of abiotic surfaces (Stanley, 1983;Fletcher, 1988;Lopez-Lopez et al, 1991;Ohmura et al, 1993;Reid et al, 1994;Makin and Beveridge, 1996). We tested the ability of the wild type and selected mutants to form biofilms on relatively hydrophobic surfaces (PVC, polycarbonate and polypropylene) and a relatively hydrophilic surface (borosilicate glass).…”
Section: Isolation Of Mutants Defective In Biofilm Formationmentioning
confidence: 99%
“…Biofilm bacteria are markedly different from their planktonic counterparts, as judged by gene expression, cellular physiology and the biofilm cells' increased resistance to antibiotics (Hoyle and Costerton, 1991;Costerton et al, 1995). Numerous reports have documented the ability of diverse bacterial species to form biofilms on a variety of abiotic surfaces of great importance in medicine and industry (Stanley, 1983;Fletcher, 1988;Lopez-Lopez et al, 1991;Ohmura et al, 1993;Reid et al, 1994;Makin and Beveridge, 1996). Previous studies exploring biofilm formation have generally focused on identifying the organisms that comprise biofilms, their physical and chemical properties and the architecture of the biofilm (Costerton et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to other Acidithiobacillus species, A. thiooxidans is thought to develop a mechanism that facilitates the attachment of cells to the surface of sulfur/sulfidic particles (Andrews, 1988;Konishi et al, 1995). Previous studies have shown that the attachment involves the effect of electric charges, surface irregularity, and cell membrane characteristics (Ohmura et al, 1993;Solari et al, 1992). In addition, it involves the excretion of extracellular polymeric substances (EPS), which are thought to mediate the contact between the cell and the surface (Bhavaraju et al, 1993;Kumar et al, 1991).…”
Section: Introductionmentioning
confidence: 99%